A LINGUODIDACTIC ANALYSIS OF LISTENING COMPREHENSION AND SPEAKING SKILLS IN ENGLISH LANGUAGE TEACHING - Barchinoy Sultanova Davronovna (International Journal of Literature and Language Studies, 2026)
In recent years, the integration of multiple teaching skills - particularly the synergistic combination of pedagogical competencies - has emerged as a salient trend within the field of applied linguistics and English Language Teaching (ELT). A growing body of scholarly work has been dedicated to exploring how the deliberate fusion of instructional strategies, assessment literacy, classroom management, and technology-mediated instruction can enhance learner outcomes. Consequently, an increasing number of researchers and practitioners have devoted considerable time and expertise to advancing ELT methodologies. Their insights have not only enriched academic discourse but have also empowered young language learners and early-career teachers, fostering more dynamic and effective learning environments.